Dramaturgically nondescript spectacles, or considerations on the happiness - Kowalska, Anna (Hybris, 2012)
The aim of the paper is to consider the concept of the happiness. The text refers to several literary examples of the happiness and characterizes “the spectacles of the happiness”. It shows (in the context of Blanchot’s words) manifold destructive practices associated with the happiness with reference to everyday life. The paper compares the life to the structure of the spectacle and analyses “the spectacles of the happiness” in the context of Goffman’s theory (scene and wings, shown and hidden activities). The article expresses criticism of the vision of life based on the spectacular happiness.